Ontogenetic shifts in bait preference and foraging behavior of invasive Pterygoplichthys spp. - Lendri Lendri; Zulkarnain Zulkarnain; Am Azbas Taurusman; Ronny Irawan Wahju; Mulyono S Baskoro (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
The invasive suckermouth catfish (Pterygoplichthys spp.), native to South America, poses ecological threats in non-native freshwater systems. However, effective natural baits for its control remain understudied. This study evaluated the behavioral responses of three size classes (<10 cm, 25 cm, >35 cm) to two baits—Lumbricus rubellus (earthworm) and Loligo sp. (squid) and assessed bait durability via protein and fat leaching over 15 hours. Using 32 CCTV-monitored trials, significant ontogenetic differences were observed (p < 0.05): juveniles responded most actively (10 and 9 approaches), adults avoided earthworms but approached squid moderately (5 times), and larvae showed intermediate responses. Though earthworms induced a faster mean response time (20:19 min), it was not statistically different from squid (p = 0.79). Biochemical analysis revealed superior nutrient retention in L. rubellus (protein: 10.78%, lipid: 9.90%) compared to rapid leaching in squid. The findings suggest that L. rubellus is a highly effective bait for catfish due to its strong chemosensory attraction and nutrient stability, supporting size-specific baiting strategies for targeted management of this invasive species.